22 cм2
Пошаговое объяснение:
Нехай 1 ст = х см, тоді друга ст. = х+3 см
за т.косинусів
х^2+ (x+3)^2 - 2x*(x+3)*cos60=7^2
x^2+x^2+6x+9-2x*(x+3)*1/2=49
x^2+x^2+6x+9-x^2-3x=49
x^2-3x-40=0
x1=8
x2= -5 -ст. кор
1 ст. = 8 cм, 2 ст = 8+3=11 см
S=1/2*8*11*1/2=22 cм2
пояснення ^2 - в степені 2
22 cм2
Пошаговое объяснение:
Нехай 1 ст = х см, тоді друга ст. = х+3 см
за т.косинусів
х^2+ (x+3)^2 - 2x*(x+3)*cos60=7^2
x^2+x^2+6x+9-2x*(x+3)*1/2=49
x^2+x^2+6x+9-x^2-3x=49
x^2-3x-40=0
x1=8
x2= -5 -ст. кор
1 ст. = 8 cм, 2 ст = 8+3=11 см
S=1/2*8*11*1/2=22 cм2
пояснення ^2 - в степені 2